2010
DOI: 10.1021/jp1026477
|View full text |Cite
|
Sign up to set email alerts
|

Supported Lipid Bilayers on Mica and Silicon Oxide: Comparison of the Main Phase Transition Behavior

Abstract: The usual biophysical approach to the study of biological membranes is that of turning to model systems. From these models, general physical principles ruling the lateral membrane structure can be obtained. A promising model system is the supported lipid bilayer (SLB) which could foresee the simultaneous investigation of the structure and physical properties of lipid bilayers reconstituted with membrane proteins. A complete exploitation of the model system to retrieve biologically relevant information requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 43 publications
(98 reference statements)
6
93
1
Order By: Relevance
“…While future work will be needed to establish that such factors affect AuNP insertion, there is some evidence in existing experimental results that supports the idea that enhanced lipid fluctuations reduce the barrier for AuNP insertion. In this study, hard substrates were used to support the planar lipid bilayers that may reduce lipid mobility by stabilizing the contacting lipid head groups 57,58 . This effect likely reduced the probability of tail protrusions, further limiting the insertion of AuNPs into the defect-free bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…While future work will be needed to establish that such factors affect AuNP insertion, there is some evidence in existing experimental results that supports the idea that enhanced lipid fluctuations reduce the barrier for AuNP insertion. In this study, hard substrates were used to support the planar lipid bilayers that may reduce lipid mobility by stabilizing the contacting lipid head groups 57,58 . This effect likely reduced the probability of tail protrusions, further limiting the insertion of AuNPs into the defect-free bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case a strong coupling between the two leaflets could be the reason for the same lateral mobility. We recently demonstrated that the interleaflet coupling is strongly related to the experimental details of the sample preparation, including preparation temperature and the type of support (Seeger et al, 2009b;Seeger et al, 2010). So, it is not always possible to compare the obtained results even if related to the same system.…”
Section: Chapter 1: Supported Lipid Bilayers With Reconstituted Membrmentioning
confidence: 99%
“…It is noted that the change of the diffusion mode occurred at approximately the main-phase transition temperature determined from the diffusion coefficients measured via z-scan FCS. Examination of the data for the glass-supported bilayers suggests similar results, with the change in the diffusion mode potentially occurring near the measured main-phase transition temperature of 24.3 C. However, the uncertainty of the data in the temperature range of [20][21][22][23][24] C prohibits any absolute statements about the diffusion behavior. Regardless, it is clear that there is a substrate-dependent difference in behavior in the [20][21][22][23][24] C temperature range when comparing the actin-supported and glass-supported bilayers.…”
Section: Biophysical Journal 108(8) 1946-1953mentioning
confidence: 59%
“…The diffusion coefficients for the glass-supported membranes (Fig. 3, triangles) also increased with temperature, but over a more narrow range (22)(23)(24)(25)(26)(27)(28)(29)(30) C). The main-phase transition temperature for each model membrane was determined via …”
Section: Resultsmentioning
confidence: 89%